Screening and Identification of Fibrinolytic Bacteria From Tauco - Setyawati, Eni; Poernomo, Achmad Toto; Sudjarwo, Sudjarwo (Berkala Ilmiah Kimia Farmasi, 2022)
Tauco was one kind of traditional fermented food from Indonesia. Tauco was processed from soybean paste with a salty taste and commonly had yellow and black colors. Generally, tauco was used as a spice or seasoning in various daily dishes. The study aimed to find and identify the bacteria that produced fibrinolytic enzymes in tauco. The sample used in this research was tauco from six different manufacturers. Two tests were conducted in this study: a proteolytic test on Skim Milk Agar and a fibrin plate test. Both tests were used to identify the bacteria producing fibrinolytic enzymes. The bacteria were identified macroscopically, through gram staining, and by 16S rRNA sequencing. In the proteolytic test, the sample was diluted with 0,9% NaCl to 10^-7 and then inoculated on Skim Milk Agar medium, incubated at 37ºC for 24 hours. The samples had proteolytic activity, which was shown by the formation of clear zones around the bacteria. Seventeen isolates of proteolytic bacteria were incubated at 37ºC for 24 hours and then used for the fibrin plates. All proteolytic bacteria produced fibrinolytic activity, with the most extensive fibrinolytic index in the TC4a isolate of 3,46. Furthermore, TC4a bacteria were genotypically identified by sequencing the 16S rRNA gene. According to the results of tauco identification, the bacteria that strongly produced fibrinolytic enzymes in the tauco sample TC4a were found to be similar to Bacillus cereus TC4a.Keywords: Fibrinolytic enzyme, Fibrinolytic activity, Tauco, Screening, identification, 16s rRNA, Bacillus cereus